Evaporation enhancement from surface heating - Duan, Fei (2013)
Evaporation is observed when heat conducts from the interface to the gas and liquid phases at a heated flat surface by two aligned heating elements. The average evaporation flux is significantly higher than that while the water surface is heated below under the same power input. To demonstrate the energy transport at an interface with zero cross-section area from a high-temperature position to a low-temperature position, a thermodynamic model is derived from the Gibbs dividing-surface approximation. The measurement shows that the interfacial temperature is up to 6.9 °C higher at the heating wires than that at the centerline between the two heating wires as the liquid is heated at the surface. The induced interfacial flow can transport energy to maintain the evaporation by overtaking negative thermal conduction to the evaporating interface globally.